Current Biological Insights of Castanea sativa Mill. to Improve Crop Sustainability to Climate Change - Tiago Marques; Andrea Ferreira-Pinto; Pedro Fevereiro; Teresa Pinto; José Gomes-Laranjo (Plants)
The sustainability of agriculture is seriously threatened by climate change. In Europe, chestnut ecosystems, which are growing mainly in Mediterranean climate, are facing during summertime increasing of heat and drought stresses. These induce fragilities on trees, leading to a reduction in productivity and predisposing them to pest and disease attacks. The plasticity of chestnut species under contrasting climate is known. Understanding the specific adaptation of cultivars to different climate features is now important to anticipating climate changes. Caucasian Region is considered the origin center of chestnut (Castanea sativa), which is characterized by climatic transition from the Mediterranean to the Euro-Siberian area. Mostly, areas of chestnut are concentrated in the countries around the Mediterranean Basin, thriving in regions with humid and Pré-Atlantic bioclimates. In Portugal, more than 95% of the chestnut area is located in the Center and North side of Portugal. This is an anisohydry species, characterized by good hydroplasticity: 90% reduction in A occurs when Ψwstem drops to −1.25 MPa, and a 50% reduction in A occurs at values of −1.7 MPa. The highest fatty acid contents in chestnut chloroplasts are a-linolenic acid (18:3), ranging between 40 and 50% of the total amount and being the unsaturated/saturated 2.27 for Longal. New strategies are being investigated in order to increase tolerance against those abiotic factors in chestnut species. They include the use of innovative irrigation techniques, which can increase production 22–37%. Fertilization with silicone (Si) has been investigated to promote the tolerance of plants against heat and drought stresses. Breeding programs, mostly (in Europe) against ink disease, have been performed since the middle of the XX century to create new genotypes (such the Portuguese ColUTAD®). ClimCast, a network of orchards, was created in Portugal with the aim of responding to the new challenges facing orchards in the context of climate change.